YOUTUBE-SOURCED VIDEOS AS TEACHING MEDIA FOR LISTENING COMPREHENSION: AN OPTIMIZING OF AUTHENTIC-UPDATED LEARNING SOURCE - Rustam; Muhammad Danial (English Language, Linguistics, and Culture International Journal, 2022)
The development of Information and Communication Technology (ICT) is globally unavoidable since it becomes a booster for all life aspects, including but not limited to teaching and learning. Internet provides limitless resources teaching and learning media, one of those are videos in YouTube. The objective of this study is to know, whether or not YouTube media can improve students’ listening skill in English teaching. The subject of the study was eleventh grader (11) SMK Negeri 2 Majene. The total population is 65 students from two classes, as the sample is consisted of 30 students. In this study, researcher used quantitative method on pre-Experimental research, with one group pre-test and post-test. The pre-test result was compared to the post-test result to determine whether or not the trajectory is successful. This research uses quantitative research. Result from pre-test to post-test students can hear English well. Thus, using YouTube media in learning process is effective to improve students’ listening ability. This is proved by the mean score of pre-tests which is 17 and post-test obtained score of 30.1. That means the ability to listen to students increase 13.1 points. T-test value is 6,89 and T-table is 1,699 with degree of freedom (df) 29 and significant level at 5% is 1,699. Based on the analysis data, alternative hypothesis (HI) in this research is accepted because the result of T-value is higher than T-table (6.89> 1.699). It indicates that YouTube media can be effectively applied in learning English for the 11th students in SMK Negeri 2 Majene.